An integration of slicing, NFV, and SDN for mobility management in corporate environments - Meneses, Flávio (2019)
Online access to information while on the move has conferred businesses with the capability to be constantly accessible and in operation, independently of geographical area or time zone. There are situations, however, that demand technical solutions for specific scenarios, such as controlled access to corporate-based content. Virtual Private Networks (VPNs) allow controlled remote access to con-tent, supporting scenarios such as teleworking. Nonetheless, such mechanisms are not commonly associated with the highly mobile users of today, which can traverse different types of access networks, while still keeping access to con-tent restricted to corporate network usage. In addition, as VPN mechanisms are disassociated from mobility procedures, service disruption can happen or specific mechanisms and clients can be required in end-user's equipment. This paper proposes a framework that leverages Network Slicing, enabled by Software Defined Networking and Network Function Virtualisation, to provide seamless and isolated access to corporate-based content while moving through heterogeneous networks. This solution allows Mobile Network Operators to dynamically instantiate isolated network slices for corporate users, and handover them between 3GPP and non-3GPP networks while users move away from the corporate network. In this way, they are able to keep access to corporate-based content in a transparent way, while maintaining access requirements for the servicebeing used. The framework was implemented and validated over an experimental testbed composed by mobile and Wi-Fi accesses, with results presenting improvements in terms of overhead signaling and data redirection without downtime nor stream reconnection.